More than just a game : the Black origins of basketball - Moore, Madison, 1997- (Albert Whitman & Company, 2021)
"Today, the NBA is around 74% Black but, when basketball first started to catch on, it wasn't easy for Black people to play. They couldn't enter segregated YMCAs or attend privileged colleges. So Black Americans made their own spaces, playing in dance halls before the dancing started, and eventually forming teams called the Black Fives. More than Just a Game celebrates the history of basketball from a Black perspective, revealing how it changed Black communities and how they made the sport into what it is today"--